Analysis of project work using earned value management and precedence diagram method in manufacturing system projects - Nugroho, Dizsa Arliansyah; Sukmono, Tedjo; Jakaria, Ribangun Bamban (Universitas Mercu Buana, 2024)
PT. Weiss Tech has received a project order for the fabrication and installation of coffee packaging production machines from PT.XYZ, scheduled to start on June 19, 2023, with a deadline of June 24, 2024, spanning 54 weeks. The project has been ongoing for 16 weeks with an update indicating that only 20% of the planned progress has been achieved, which suggests that it may not be completed on time. To evaluate the project's performance, the EVM method will be used to identify critical tasks and reduce the project duration using the Precedence Diagram Method with the help of MS Project software. The evaluation shows negative values for CV and SV variances, as well as performance index SPI<1 and CPI<1, indicating poor project performance. The critical tasks identified include electrical & instrument installation, machine & utility installation, trial work, assembly, quality control, polishing, milling, turning, cutting, and design. Design work has been identified as the most influential on the critical path. By rescheduling the project plan, positive values for CV and SV have been achieved. With the SPI value of 1.13 and CPI value of 1, it can be concluded that future project performance will be completed faster and within budget.